2015
DOI: 10.1007/s13197-015-1756-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hydrocolloid on rheology and microstructure of high-protein soy desserts

Abstract: Due to the rheological and structural basis of texture perceived in semisolid foods, the aim of this work was to study the effects of two thickening agents, on rheology and microstructure of soy protein desserts. As rheological parameter values may not be enough to explain the possible perceived texture differences, the effect of composition on two instrumental indexes of oral consistency (apparent viscosity at 50 s −1 and complex dynamic viscosity at 8 Hz) was also studied. Samples were prepared at two soy pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…This species contained higher contents of galacturonic acid and fucose than the other two Iranian GT species. Moreover, the values obtained in this study for flow behavior parameters are in agreement with those found by other studies for various food desserts with added hydrocolloids such as starch, chickpea flour, carboxymethyl cellulose, carrageenans, agar-agar, and xanthan gums (Aguilar-Raymundo and Vélez-Ruiz, 2018; Arancibia et al, 2015;Oroian, 2013). Figure 1A depicts the flow behavior of Samples 1, 2, 4, 8, and 9 on which sensory evaluation was performed.…”
Section: Resultssupporting
confidence: 91%
“…This species contained higher contents of galacturonic acid and fucose than the other two Iranian GT species. Moreover, the values obtained in this study for flow behavior parameters are in agreement with those found by other studies for various food desserts with added hydrocolloids such as starch, chickpea flour, carboxymethyl cellulose, carrageenans, agar-agar, and xanthan gums (Aguilar-Raymundo and Vélez-Ruiz, 2018; Arancibia et al, 2015;Oroian, 2013). Figure 1A depicts the flow behavior of Samples 1, 2, 4, 8, and 9 on which sensory evaluation was performed.…”
Section: Resultssupporting
confidence: 91%
“…A 15 μl aliquot of the resulting emulsion was added to 1 ml of distilled water, stirred gently, and then a single drop was poured onto a glass-slide and observed via fluorescent microscope (LEICA DM 3000, Power: ebq 50 qc, USA) attached with a LEICA DFC 450C camera. The 568 nm laser line was used for excitation, inducing a fluorescent emission of Rhodamine B (Arancibia et al 2015), detected between 600 and 700 nm (Vasbinder et al 2003). Average droplet size (μm) was measured by ImageJ® software and represented by d 32 (Karaca et al 2011).…”
Section: Emulsion Microstructure By Fluorescent Microscopymentioning
confidence: 99%
“…fragrance and flavoring oils), surfactants, salts or proteins. [10][11][12] A general challenge in formulating such complex systems is to understand the interactions between the components and their effects on the efficacy and the stability of the product over its shelf-life.…”
Section: Introductionmentioning
confidence: 99%
“…12 Despite its broad use in industry, Na CMC behavior in solution is still relatively poorly understood and is the subject of research from both fundamental 1,[13][14][15][16] and applied perspectives. 10,[17][18][19][20] The polyelectrolyte nature of Na CMC is, in itself, a reason for this poor understanding since many questions remain about the behavior of charged polymers in solution, 16,21 and especially in saltfree solutions; one example concerns the origin of the 'slow' relaxation mode typically observed using Light Scattering (LS), whose presence is not predicted by standard theory. [22][23][24] Given the biological origin of Na CMC, it typically has a high polydispersity of the chain length distribution 1,5,25,26 (common values of Mw/Mn are around 1.7-4.5 1,5,13,25,26 ).…”
Section: Introductionmentioning
confidence: 99%